Research on Extended L-Band Frequency Coordination Scheme in Mobile Direct Connection to NGSO Satellite Service - Lichong WANG; Chenhua SUN; Weisong ZHAO; Quan LIU; Shan LU (天地一体化信息网络)
At present, the frequency of non-geostationary orbit(NGSO) mobile satellite service is becoming more and more tense.Aimed at the complicated problem of frequency coordination of mobile direct connection to NGSO satellite service, firstly, an analysis was conducted on the current frequency usage status and trends of mobile direct connection to NGSO satellite service.Secondly, the frequency coordination scheme between mobile direct connection to NGSO satellite service and other same frequency space services in extended L-band was analyzed and studied.By analyzed the frequency coordination of mobile direct connection to NGSO satellite service in extended L-band, the space services that need to carry out frequency coordination work with mobile direct connection to NGSO satellite service were determined.The basic frequency coordination scheme of mobile direct connection to NGSO satellite service with each space service was studied and the coordination scheme suggestions were given, at the same time, the interference analysis and calculation involved in the specific coordination scheme were listed for example.The above research can be used as reference for the research of frequency coordination of mobile direct connection to NGSO satellite service system, as well as for the next step research of key technologies related to mobile direct connection to NGSO satellite service.